2022
DOI: 10.3390/plants11131771
|View full text |Cite
|
Sign up to set email alerts
|

Phenoplasticity of Essential Oils from Two Species of Piper (Piperaceae): Comparing Wild Specimens and Bi-Generational Monoclonal Cultivars

Abstract: This study tested the hypothesis that “clonal chemical heritability is a crucial factor for the conservation of chemical uniformity of Piper essential oils in controlled monoclonal cultivation”. We asexually propagated first and second-generation clones of two medicinal and aromatic species, Piper gaudichaudianum Kunth and Piper mollicomum Kunth (Piperaceae), for use as experimental models since they show high chemical plasticity in the wild. Leaves from wild specimens of both species, and their respective cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…This study identified and quantified the constituents of the EO from the leaves of P. lhotzkyanum in different temporal variations, with a predominant majority of sesquiterpenes. As for the predominance of this class, it is in accordance with other studies carried out with other Piper species [5][6][7]26].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study identified and quantified the constituents of the EO from the leaves of P. lhotzkyanum in different temporal variations, with a predominant majority of sesquiterpenes. As for the predominance of this class, it is in accordance with other studies carried out with other Piper species [5][6][7]26].…”
Section: Discussionsupporting
confidence: 91%
“…The emission of volatiles is highly regulated and restricted to specific times of day, seasons of the year, and phenology, in many plant species [23]. This phenomenon has also been observed in the Piper genus [6][7][8]24], which suggests that these plants have the ability to regulate metabolic, physiological, and developmental processes through their biological clock [20,21,25].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations